Factors Associated with Hindrance to Lowering Blood Pressure in Hypertensive Prolanis Patients at Ajibarang I Public Health Care Center Banyumas Regency - Sovi Haswindha Putri Nugraheni; Retno Sulistiyowati; Umi Solikhah; Kurnia Ritma Dhanti (Science Midwifery, 2022)
Hypertension is a condition of abnormal and continuous increasing blood pressure, which has been checked several times. It is caused by some risk factors so that blood pressure cannot be maintained properly. The risk factors for hypertension that cannot be changed include age, gender, and genetics. Modifiable risk factors include smoking, a low fiber diet, dyslipidemia, and excessive salt consumption. In particular, dyslipidemia is a metabolic disorder characterized by an increase in total cholesterol, LDL, triglycerides, and HDL. Individuals who suffer from hypertension must receive regular care. One is by following Prolanis, so their high blood pressure does not cause disease complications. This study aimed to determine what factors were associated with hindrance to lowering blood pressure and the relationship of HDL levels and physical activity with blood pressure in patients with hypertension Prolanis at Ajibarang Public Health Center I. This quantitative research utilized the total sampling technique and the method of examining HDL levels of precipitation. The study was conducted in June 2022. It is shown that the relationship between HDL levels with systolic blood pressure and diastolic blood pressure were p = 0.870 and p = 0.870, respectively. Meanwhile, the relationship between physical activity and systolic blood pressure and diastolic blood pressure were p = 0.055 and p = 0.754, respectively. It meant that there was no relationship between HDL levels and physical activity with blood pressure in hypertension Prolanis patients at Ajiabarang Public Health Center I.